Blood urea nitrogen to creatinine ratio and long-term survival in patients with chronic heart failure - Yajiao Wang; Xia Xu; Shuqing Shi; Xiya Gao; Yumeng Li; Huaqin Wu; Qingqiao Song; Bingxuan Zhang (European Journal of Medical Research, 2023)
Abstract Objectives To explore the correlation between Blood urea nitrogen to creatinine ratio (BUN/Scr ratio) and prognosis of patients with chronic heart failure complicated with renal injury. Methods A retrospective analysis of 504 patients hospitalized in Guang 'anmen Hospital, Chinese Academy of Traditional Chinese Medicine from March 2006 to June 2014 was conducted. The baseline data were analyzed, and the cutoff value was obtained by receiver operator characteristic curve (ROC) analysis, according to the cutoff value, all the participants were divided into two groups, BUN/Scr < 19.37 group (280 cases) and BUN/Scr ≥ 19.37 group (224 cases). The main end point was defined as all-cause death. The long-term mortality of the two groups was evaluated, and Kaplan–Meier survival curve was drawn. Univariate analysis was performed on all the variables affecting the patient's prognosis, and the variables with P < 0.05 were put into Cox regression model, and subgroup analysis was performed on the variables that might affect the patient’s prognosis. Results The baseline data of 504 patients were analyzed and found that the median follow up was 683. Through ROC analysis of 504 subjects, the cutoff value of BUN/Scr was 19.37. The results of Kaplan–Meier survival curve showed that the mortality rate of patients with ratio ≥ 19.37 was higher than that of patients with ratio < 19.37. After multivariate analysis, COX regression model showed that the mortality of patients with BUN/Scr ≥ 19.37 was 1.885 times that of patients with BUN/Scr < 19.37 [HR = 1.885 (1.298–2.737), P = 0.001]. Subgroup analysis showed that the relationship between BUN/Scr and the prognosis of CHF was influenced by NYHA and eGRF (P < 0.05). Conclusions BUN/Scr ratio is related to the poor prognosis of patients with CHF, and is an independent predictor of all-cause death.